Fish Disease Outreach Messages: Testing of Gain and Loss Frames - Erin L. Pavloski; Heather A. Triezenberg ([TEST] Journal of Extension, 2021)
Gain and loss framing has been used as a technique in risk communication to shape individuals’ behaviors in many fields. Our community-engaged research, conducted in partnership with the Michigan Department of Natural Resources (MDNR), experimentally tested five message frames to determine efficacy for outreach programs. We found: a) to increase risk perceptions of fish disease use a loss frame in a management context, b) to decrease risk perceptions of fish disease management use a gain frame in a disease context, and c) to motivate behavioral intentions for prevention and risk reduction use a gain frame in a disease context.
Keywords: message framing; outreach; fish disease; Great Lakes region; aquatic invasive species